Adsorbable and Antimicrobial Amphiphilic Block Copolymers with Enhanced Biocompatibility - Cornelia Wolf‐Brandstetter; Rafael Methling; Dirk Kuckling (Macromolecular Materials and Engineering)
Abstract To minimize or avoid the use of antibiotics, antimicrobial polymers have emerged as a promising option to fight biomaterial‐associated infections, e.g., on titanium‐based implants. However, the challenge is to develop active polymers that exhibit an antimicrobial effect and are compatible with human cells. Different studies aiming for biocidal polymers active in soluble mode, focused on the ratio of cationic to hydrophobic groups, while only marginal knowledge is available for immobilized components. Here a strong hydrophilic electrolyte 4‐vinylbenzyltrimethylammonium chloride (TMA) is chosen as the cationic component. The block composition of the polycationic segment is modified with styrene (Sty) regarding the amphiphilic balance. To adsorb such polymers onto titanium surfaces they are equipped with a polyphosphonic acid anchor block by sequential reversible‐addition‐fragmentation chain‐transfer polymerization (RAFT) polymerization. The polymer composition affected the wetting behavior of adsorbed coatings with water contact angles ranging from 17° to 72°, while zetapotential measurements confirmed high extent of positive charges for all adsorbed polymer coatings. The fundamentally modified block composition resulted in significantly improved cytocompatibility. Antimicrobial efficacy in early bacterial adhesion is still retained from slightly antiadhesive coatings to combined antiadhesive/biocidal activity depending on Sty/TMA ratio in random polymers while a block copolymer revealed lowest antimicrobial effect.